Two-Year Follow-up on the Use of Absorbable Mesh Plates in the Treatment of Medial Orbital Wall Fractures - Jae-Pil You (Archives of Plastic Surgery, 2013)
Background Absorbable materials offer many advantages in the reconstruction of orbital walls; however, the possibility of postoperative enophthalmos after complete absorption cannot be excluded. We evaluated the postoperative results of absorbable mesh plates used as onlay implanting on the medial orbital wall to determine whether they are suitable for medial orbital wall reconstruction. Methods The study included 20 patients with medial orbital wall fractures who were followed up for more than 2 years postoperatively. We used absorbable mesh plates in all of the patients. We measured the following: the changes in the expanded orbital volume by comparing the preoperative and postoperative computed tomography (CT) scans and the degree of clinical enophthalmos. Results There were no major complications associated with the use of absorbable materials such as infection, migration, or extrusion of mesh plates during the long-term follow-up. The orbital volumetric changes between the preoperative and postoperative CT scans were not statistically significant. However, the expanded orbital volume was not related to the degree of clinical enophthalmos. Conclusions The reconstructed orbital wall may provide supportive scar tissue to the orbital contents even after the absorbable materials have dissolved completely. Absorbable mesh plates could be another option for the reconstruction of the medial orbital wall.